Trends and Research Opportunities For Microcontroller-Based Flood Warning Systems: A Bibliometric Analysis - Aulia Isti; Asrizal Asrizal; Harman Amir; Leni Aziyus Fitri (Department of Physics, Universitas Negeri Padang, 2026)
Indonesia as an archipelago has a high level of vulnerability to flood disasters, which is worsening due to climate change, rapid urbanization, and weak mitigation systems. Ideally, an early warning system that is responsive, accurate, affordable and easy to implement in vulnerable areas is needed. While microcontrollers offer a potentially effective technological solution, most research is still limited to small prototypes without regard to long-term predictability or community participation. This study aims to evaluate the development, focus, and prospects of microcontroller-based flood warning system research using a quantitative bibliometric approach. A total of 200 articles from 2015-2025 were collected through Publish or Perish and analyzed using VOSviewer. The results showed, first, a significant increase in publications occurred in 2024, namely 29 articles. Second, word network visualization resulted in the mapping of 87 keywords in 7 clusters. Third, data overlay visualization resulted in a shift in focus to IoT integration, the latest microcontrollers, cloud-based monitoring. Fourth, data density analysis confirms the dominance of technical aspects, where keywords such as microcontroller, flood early warning system, and flood become the center of attention with the highest density level. The implications of these findings provide direction for the development of a more adaptive, inclusive, and applicable flood warning system in disaster mitigation.